Organizational Logic for Concurrent Government in Metropolitan Areas - Boschken, Herman L. (Academy of Management Review, 1976)
In an urban environment of high diversity, governmental structure should be open and multinucleated to meet the performance criteria of efficiency and effectiveness. A case study of the Lakewood Plan illustrates that governmental structure is contingent upon environmental factors in the specific metropolitan area. The traditional “one best way” recommendation for consolidation assumes an oversimplification of the urban public economy.